VERB HYPONYMY CONTAINING THE MEANING OF 'TO TAKE' IN BETAWI MALAY LANGUAGE - Ririen Ekoyanantiasih (Balai Bahasa Jawa Barat, 2015)
IN Betawi Malay language there are many lexemes which have similar relationsof meaning. Some of which belong to synonymy while others belong to hyponymy.This article emphasizes the hyponymy of the verbs containing the meaning of